PENGARUH TERAPI SSBM TERHADAP PERUBAHAN TD PADA LANSIA DENGAN HIPERTENSI DI BSLU MANDALIKA NTB - Citra Sepriana (STIKES Mataram, 2019)
Being old is the phase of life that every single human at the age of 60 or above faces. The more the age, the more problem of physical problem, mental change and psychological change as the process of being old. This research is aimed at determining the effect of slow stroke back massage therapy on the change of blood pressure of elderly with hypertension in Elderly Social House of Mandalika NTB. 20 respondents had hypertension were elected as samples through total sampling. This research is designed to use pre-experimental one group pretest-posttest. Research instruments using observation sheets, needle sphygmomanometers, stethoscopes and SSBM guidelines. The data were collected through observation sheet and analyzed with wilcoxon signed ranks. The results showed that most were at the age of 60-74 years, mostly female genders, and most were not in school, treatment was administered for 7 days in respondents, most of the respondents had changed Decrease in blood pressure, and a small part suffered permanent blood pressure because the respondent is not in the situation of relaxation when administered therapy. It is inferred that there is effect of slow stroke back massage therapy on the change of blood pressure of elderly with hypertension in Elderly Social House of Mandalika NTB.